Intervention Research in Educational Practice Alternative Theoretical Frameworks and Application Problems - Astleitner, Hermann (Waxmann Verlag, 2020)
Improving learning and teaching at schools or universities may start with choosing evidence-based interventions and practices, but does not end there. To ensure sustainable changes to programs in educational practice, interventions need to address complex issues related to theories, research designs, and measurements. This book presents typical but often overlooked problems in intervention research in educational practice. These problems are embedded in various educational areas such as, amongst others, school effectiveness, instructional design or motivational aspects of teacher trainings.